PRE-SERVICE ENGLISH TEACHERS’ INTERPERSONAL IDENTITY IN TEACHING INTERNSHIP - Hanifah . .; Eka Nurhidayat; Afief Fakhruddin (Universitas Majalengka, 2020)
Abstract: (TPI) Teacher Professional Identity defined as self-images or self-interpretation related to people's internal systems. While the teacher constructing professional identity, it was provided a good teacher quality especially in teacher-students relationship. The teaching internship program is the program that the students implemented real teaching situations. Some of pre-service English teachers had a lack of experience in teaching, they had a lack to build positive relationships with the students as well as the interpersonal identity, and they had a lack of awareness to build their identity. The study aimed to reveal (1) how preservice English teachers build teachers-students relationship as the interpersonal identity; (2) how pre-service English teacher reflective self-evaluations during teaching; (3) how university improve students’ awareness of their identity. The study utilized qualitative research with narrative design, the instruments used observations, interviews and questionnaires. The researcher used purposive sampling with five participants to collect data. The researcher found some pre-service English teacher had positive and negative relationship as well as desirable and undesirable interpersonal identity. Pre-service English teacher beliefs, teachers’ roles, and implemented of ICT were discussed in result. After pre-service English teachers finished the internship program, they had realized to evaluate their selves as a whole become future teachers.Keywords: Pre-service English Teachers, Teaching Internship, Teacher Professional Identity.